Peran Ayah terhadap Kejadian Stunting pada Balita di Perdesaan: Peran Ayah terhadap Kejadian Stunting pada Balita di Pedesaan - Sugianti, Elya; Putri, Berliana Devianti; Buanasita, Annas (Universitas Airlangga, 2024)
Background: Stunting is an unresolved health problem in the world. There were 21.6% of stunted toddlers in Indonesia in 2022, with a higher proportion in rural areas than in urban areas. The mother's role mainly caused stunting. On the other hand, the role of fathers had not been reviewed much in previous research. Objectives: This study aims to analyze the role of fathers towards stunting among toddlers in rural areas. Methods: The study had a case-control design conducted from April to October 2019. This research involved two populations, namely the control population and the cases. The control population was all non-stunted toddlers aged 24-59 months who lived in Jombang Regency, while the case population was all stunted toddlers aged 24-59 months who lived in Jombang Regency. The authors applied a multistage random sampling. The sample consisted of 79 controls and 79 cases calculated based on the two-population proportion formula. Data were analyzed using the chi-square test, fisher exact test, and logistic regression with α = 5%. Results: Fathers with low education increased the risk of toddlers becoming stunted 2.407 times higher than fathers with high education (p = 0.010; OR = 2.407; 95% CI = 1.231-4.705). Fathers from large families were 1.971 times more likely to have stunted toddlers than fathers from small families (p = 0.042; OR = 1.971; 95% CI = 1.026-3.785). Conclusions: Stunting in toddlers was significantly influenced by father's education. The size of the family also affected a toddler's risk of stunting. Increasing school age should be a priority program for preventing stunting in rural areas. In addition, health campaigns regarding pregnancy planning and birth control need to be carried out on an ongoing basis to reduce the incidence of stunting.